Integrating Social and Political Strategies as Forms of Reciprocal Exchange into the Analysis of Corporate Governance Modes. (10th November 2017) - Boddewyn, Jean J.; Buckley, Peter J.
Abstract: The concept and theory of reciprocity provide fruitful ways of integrating social and political strategies because both involve donating valuable resources to non‐market recipients – mainly non‐governmental organizations, politicians and regulators – who are not contractually bound to reciprocate although a return is normally expected. Besides, we interpret the use of non‐contractual reciprocity through relational‐models theory and transaction‐cost economics. The former offers a model of 'equality‐matching' that corresponds to reciprocity while transaction‐cost economics' criteria of uncertainty, frequency and asset specificity can be applied to non‐contractual relationships in order to determine their efficiency. We also differentiate reciprocity from bribery and offer research implications of the fact that goods can be obtained from others without using transactions.